Micro-flexibility: Challenges for power system modeling and control - Chatzivasileiadis, Spyros; Aristidou, Petros; Dassios, Ioannis; Dragicevic, Tomislav; Gebbran, Daniel; Milano, Federico; Rahmann, Claudia; Ramasubramanian, Deepak (My University, 2023)
This paper collects the challenges and opportunities that emerge from the millions of controllable devices – and the micro-flexibility they offer – that are deployed across the transmission and distribution systems. Moving to power systems that are dominated by converter-interfaced resources poses both threats and opportunities. On the one hand, new dynamic phenomena and types of instability arise and there is need for advanced simulation tools. On the other hand, these devices allow for a massive decentralized and direct response to disturbances. The emerging power system paradigm aims to tap the flexibility potential of the millions of controllable devices to ensure the safe operation of power systems. To achieve that, however, we first need to address a range of modeling and control challenges. This paper attempts to identify and describe these challenges.
Keywords: Granularity; Stochastic systems; Zero-inertia; Power electronics